Theodore Boone : the fugitive - Grisham, John (Grisham, John.)
On a field trip to Washington, DC, Theo spots a familiar face on the Metro: Duffy, who jumped bail and was never seen again. Theo's quick thinking helps bring Duffy back to Strattenburg to stand trial. But now that Duffy knows who he is, Theo is in greater danger than he's ever been in before. Even when everything is on the line, Theodore Boone will stop at nothing to make sure a killer is brought to justice.